Development of STEM-Based Problem Based Learning E-Module on Electrolysis Cell Material for Class XII SMA/MA - Putri Berlian Fauzi; Andromeda Andromeda (Universitas Lampung, 2022)
Abstract: Development of STEM-Based Problem Learning E-Module on Electrolysis Cell Material for Class XII SMA/MA. This study aims to develop an electrolysis cell e-module based on STEM Integrated problem-based learning. The type of research used is research and development or Research and Development (RD). The development model used is the plomp model which consists of 3 stages, namely: preliminary research (early investigation stage), (2) development or prototyping phase (development or prototyping stage), and (3) assessment phase (trial and assessment stage). This research is limited to the development stage, namely the validity test and practicality test. The research instrument used was a validity and practicality questionnaire. The E-Module was validated by 5 validators while the practicality test was carried out by 3 chemistry teachers and 16 students of class XII MIPA SMAN 10 Padang. The data from the validity test were analyzed using the Aikens'V formula and the practicality was analyzed using descriptive statistics. Validation is carried out in two stages. Stage I obtained an average content validity test of 0.76 with an invalid category and an average media validity test of 0.77 with an invalid category, so that stage II validation was carried out, where the average content validity test was 0. 91 with a valid category and the media validity test average of 0.90 with a valid category. While the practicality test for teachers is 0.91 and students are 0.91 with a very high practicality category. Thus, it can be concluded that the problem-based integrated STEM-based electrolysis cell e-module produced for class XII SMA/MA students that was developed is valid and practical.